IDENTIFICATION OF BORAX AND FORMALIN CONTENT IN WET NOODLES AND MEATBALLS IN GORONTALO CITY - Della Fatimi Modeong; Farid Buhari; Ni Luh Arwati (LPPM Universitas Bina Mandiri Gorontalo, 2022)
This study aims to determine the presence of additives in food samples in wet noodles and meatballs. The research method used is an analytical method with an experimental design (pre-experimental, the object of research is wet noodles and meatballs. Then both samples are added with formalin and borax to determine whether the two samples contain borax and formalin or not. The results showed that none of the samples contained borax. If a food contains borax, then when the food is dripped with borax (indicator) it will experience a color change to brick red. However, during the formalin test, some of these foods contain formalin, namely, wet noodles, and meatballs, where this is known from the changing color, namely when the two samples are dripped with CuSO4 there is a change in color, namely a yellowish color which indicates that the sample contains formalin.